O programa Mais Médicos e a intervenção do estado no domínio econômico para a regulação das profissões - Mouta, Luiz Fernando Picorelli de Oliveira (2016)
The article 170 of the Constitution makes it clear that the State did not opted for a model of total abstinence or full intervention, seeking the constitution to guarantee the role of private enterprise supervised by the government, in order for the economy to become an effective instrument to ensure its purpose, specifically the principle of the human dignity. The State, as a normative and regulating agent, perform the oversight, incentive and planning functions. On the other hand, social rights are rights that are guaranteed by various means, including the regulation of economic relations, giving everyone the benefits of life in society. Such rights, the right to health, is everyone's right and it is also a duty of the state, guaranteed through social and economic policies. To ensure the right to health for all, it was created the Unified Health System. However, in reality, the Unified Health System was not able to avoid the large concentration of establishments, structure and health professionals in the South and Southeast regions, to the detriment of other areas of the country. This was compounded by the State's abstention when it comes to planning and regulation of the medical profession, which is predominantly carried out by the Federal Medical Council and Regional Medical Councils. The "More Doctors" program, established by Law nº. 12 871 2013, aims to expand health supply in the country by creating new courses, setting new standards for medical education in the country and the promotion in the priority areas of medical improvement of Unified Health System in primary care area in health. Therefore, the "More Doctors" program, despite some flaws, is constitutional from the perspective of economic order, since it preserves the right to health by legitimate state intervention in the economic domain, and it is in line with the principle of reduction social and regional inequalities and the principle of human dignity